Identifikasi Komponen Bioaktif dan Aktivitas Ekstrak Rumput Laut Merah (Eucheuma spinosum) - N Ira Sari; Andarini Diharmi; Santhy Wisuda Sidauruk; Febriani Melisa Sinurat (Jurnal Teknologi dan Industri Pertanian Indonesia, 2022)
Eucheuma spinosum is a species of red seaweed that has the potential as an antimicrobial compound due to the presence of active saponins and flavonoids.  This study was aimed to determine the bioactive and antimicrobial components of the crude extract of E.spinosum.  This study was used an experimental method, by extracting E.spinosum by maceration using methanol as a solvent. Analysis parameters were consisted of the identification of bioactive and antimicrobial components against Eschericia coli and Bacillus subtilis. The results were showed that the crude extract of obtained biaoctive components, respectively, flavonoids, alkaloids, steroids, and saponins. The results of the analysis of the crude extract of E. spinosum against Eschericia coli and Bacillus subtilis showed that the extract was able to inhibit the growth of both types of bacteria. The inhibition of E.spinosum extract against B.subtilis bacteria is classified as moderate to strong because it had an inhibition zone of 9.00-14.00 mm, and E. coli was  in the moderate category of inhibition zone 6.7-8.83 mm